Cryptococcus neoformans causing meningitis in AIDS patients - Everardo Albuquerque Menezes; Maria Neuman Ricarte Monteiro; Maria Rozelê F. Angelo; Cintia Duarte Santos; Caio César Furtado Freire; Francisco Afrânio Cunha (Sociedade Brasileira de Medicina Tropical (SBMT), 2002)
Cryptococcus neoformans causes meningitis in AIDS patients. In the São José Hospital, reference center for patients with AIDS in Fortaleza - Ceará State - Brazil, 54 samples of the cerebrospinal fluid were analyzed from January 1st through December 31st 2000. Direct examination with India ink and culture in Sabouraud's agar at 37°C were done. Of the specimens studied 5(9.25%) were positive.